Extraction of Antioxidant Peptides and Activity Evaluation of Frog (Rana nigromaculata) Skin by Ultra-high Pressure Assisted Enzyme Hydrolysis - Xicai ZHANG; Rong LI; Yechuan HUANG (Shipin gongye ke-ji)
In order to improve the comprehensive utilization value of the skin of the frog (Rana nigromaculata), the extraction process of antioxidant peptides of the skin of the frog (Rana nigromaculata) was studied in this experiment and its activity was evaluated. Ultrafiltration was used to separate the protease hydrolysis solution of the skin of the frog (Rana nigromaculata) to obtain small molecule peptides with different molecular weight. The antioxidant properties of frog (Rana nigromaculata) skin small molecule peptides were evaluated in Caenorhabditis elegans model as well as in vitro. Taking the yield of highly active small molecule peptides as the index, the response surface method was utilized to optimize the four parameters containing enzyme addition, ultra-high pressure, the action time, and liquid-to-material ratio to determine the best extraction process for small molecule peptides. Results showed that 1~2000 Da small molecule peptides possessed the optimal antioxidant effect compared to other peptides in the same molecular weight range, the scavenging capacity of DPPH free radicals and ABTS+ free radicals reached 76.93% and 59.23%, respectively. The antioxidant capacity of Caenorhabditis elegans was significantly improved. Besides, on the basis of neutral protease hydrolysis, the optimum technology parameters for secondary enzymatic hydrolysis were alkaline protease dosage 10210 U/g, ultra-high pressure pressure 315 MPa, pressure action time 9.3 min, liquid-material ratio 16 times, and the yield of small molecule peptides with 1~2000 Da was 25.26% under above condition. Ultra-high pressure assisted two-enzyme hydrolysis significantly increased the yield of small-molecule peptides from the skin of the frog (Rana nigromaculata). The results of this research provide a reference for the high-value utilization of by-products of the frog (Rana nigromaculata).